Piracy as a Violation of the Ethics of the Informatics Engineering Profession - Deni, Deni; Misnen, Misnen (Ann Publisher, 2024)
The development of information technology is high-speed. The high price of original software makes people tend to use pirated products. Viewed from the ethical side of the information technology profession, piracy is inappropriate because it violates the inventor's intellectual property rights. This article is the result of thinking to analyze the extent of software piracy. Copyright problems in software, software piracy terms, causes of software piracy, the role of software, and solutions to overcome software piracy cases. Be able to know about software copyright. As a result of this research, we can find out where the crucial points violate software piracy, the motives that exist in the case of software piracy, and the role that exists in terms of software.